Performance of the Service Sector in the Republic of Korea: An Empirical Investigation - Donghyun Park; Kwanho Shin (Asian Development Bank (ADB), 2012)
There is a widespread perception that the Republic of Korea's service sector lags behind its dynamic world-class manufacturing sector. We empirically analyze the past performance of the Republic of Korea's service sector in order to assess its prospects as an engine of growth. Our analysis resoundingly confirms the conventional wisdom of an underperforming service sector. In light of the Republic of Korea's high income and development level, the poor performance of modern services is of particular concern. We identify a number of factors underlying the poor performance, and set forth policy recommendations for addressing them. Overall, the Republic of Korea faces a challenging but navigable road ahead in developing a high value-added service sector.
hdl:11540/1256
Keywords: O14; O40; O47; 330; Services; structural change; growth; productivity; Republic of Korea; Dienstleistungssektor; Konjunktur; Produktivität; Strukturwandel; Südkorea